Endoscopic septoplasty: The open book method - Prepageran, N.; Lingham, O.R. (SPRINGER, 2010)
The advent of endoscopes has revolutionized rhinology and the traditional headlight based surgeries have largely been replaced by endoscopes. Septoplasty for deviated nasal septum or Sluder's neuralgia have been conventionally performed with the aid of headlight. This can be technically challenging as visualization of the nasal cavity, particularly the posterior portion is rather limited as the procedure is performed via the nostrils. In addition, with headlights for illumination, teaching this procedure can be difficult as only the surgeon who is wearing the headlights has direct vision of the surgical field. Endoscopic septoplasty is an accepted alternative to traditional headlight approach to septoplasty. This approach provides a direct-targeted route to the anatomic deformity, improved visualization, and magnification of the surgical field. Our experience in endoscopic septoplasty is highlighted in this paper, excluding septoplasties performed as part of exposure to the sinuses. We use the open book method that to best of our knowledge has not been described in literature before.